First record of the family Callianopsidae (Decapoda: Axiidea) and a new species of Vulcanocalliax from the Hikurangi Margin off Aotearoa New Zealand, with a key to species of Callianopsidae - Schnabel, Kareen E.; Peart, Rachael A. (Frontiers in Marine Science, 2024)
This submission is a contribution to the FMarS Research Topic 'Advances in crustacean research from the 10th International Crustacean Congress' and presents one of two research papers by the co-convenors of the congress (Schnabel & Peart, this article, and Peart & Schnabel, in prep). Both research articles cover the biology and taxonomy of endemic New Zealand deep-sea fauna, with keys that place this native fauna in a broad global context. The species descriptions included in both manuscripts are presented in honour of the organisers of the beer-brewing competition conducted during the ICC10 proceedings.